A dose-response study of aerobic training for oxygen uptake, oxidative stress and cardiac autonomic function in type 2 diabetes mellitus: study protocol for a randomized controlled trial - Verma, Shalini (Trials, 2018)
BACKGROUND: Cardiac autonomic neuropathy is a commonly overlooked complication of type 2 diabetes mellitus (T2DM) characterized by an imbalance between sympathetic and parasympathetic supply to the heart, which contributes to cardiovascular morbidity and mortality. T2DM has also been shown to negatively influence oxygen kinetics and increase oxidative stress, which may be linked to the development of various chronic complications. Aerobic training has been reported to improve oxygen uptake, antioxidant defense, and cardiac autonomic function in T2DM; however, the effects of varying doses of exercise on these variables are not known. Therefore, the aim of the present study is to explore the effects of manipulating training variables (volume and intensity) on the regulation of oxygen uptake response, oxidative stress, and cardiac autonomic function in patients with T2DM. METHODS: We will recruit 60 patients with T2DM, who will be randomly allocated into one of the three aerobic training groups: low-intensity, low-volume training; low-intensity, high volume-training; high-intensity, high-volume training; or to the control group receiving no supervised exercise. All participants will be assessed for the rate of oxygen uptake, levels of antioxidant enzymes and cardiac autonomic function at baseline and after 12 weeks of training. Secondary outcome measures will include cardiometabolic risk factors and body composition. DISCUSSION: Despite a large body of evidence on the efficacy of aerobic training in the prevention and treatment of T2DM, there is no unequivocal exercise prescription for the same. Oxygen kinetics and oxidative stress are highly sensitive to the magnitude of physical activity. It would therefore, be interesting to study their interaction with chronic exposure to various doses of exercises and explore the optimal volume and intensity to bring about improvements in these parameters. TRIAL REGISTRATION: Clinical Trials Registry – India, CTRI2017/08/009459. Registered on 23 August 2017. Retrospectively registered. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2671-y) contains supplementary material, which is available to authorized users.